A novel bipolar electrocautery‐enhanced delivery system with a lumen‐apposing metal stent for EUS‐guided drainage: A porcine study. (6th June 2022) - Jo, Seok Jung; Moon, Jong Ho; Lee, Yun Nah; Park, Jae Keun; Lee, Tae Hoon; Park, Sang‐Heum; Park, Se Ik; Jeong, Seok; Lee, Don Haeng
Abstract: Background: An electrocautery‐enhanced delivery system with a lumen‐apposing metal stent (LAMS) is available for one‐step endoscopic ultrasound‐guided transmural drainage (EUS‐TD). Bipolar electrosurgery has several potential clinical advantages, including reduced collateral thermal damage, enhanced hemostasis, and no requirement for a return electrode plate. In this study, we compared the technical feasibility and safety of a newly developed bipolar electrocautery‐enhanced delivery system with a conventional delivery system for EUS‐TD using a LAMS in a porcine model. Method: Ten days before the study, 12 mini pigs underwent common bile duct ligation for EUS‐guided gallbladder drainage. Transenteric puncture was performed, followed by placement of a guidewire. In six pigs, a bipolar electrocautery‐enhanced delivery system with LAMS (Hot SPAXUS) was inserted over the guidewire and advanced into the gallbladder, without prior dilation of the tract, by applying a bipolar cut current. In the remaining six pigs, a conventional delivery system with LAMS (Cold SPAXUS) was inserted after tract dilatation using a cystotome. The stent was removed after 4 weeks. Results: In all pigs, the stent was successfully inserted and deployed in the gallbladder without adverse events. The mean procedure time of EUS‐TD was significantly lower in the Hot SPAXUS group than that of the Cold SPAXUS group (mean ± standard deviation: 188.7 ± 5.2 vs 449.5 ± 97.5 s, P = .0019). Stent migration was not observed, and all stents were removed successfully. Conclusions: Endoscopic ultrasound‐guided transmural drainage using a bipolar electrocautery‐enhanced LAMS is feasible for reducing the procedure time while maintaining the high success rate and safety of conventional LAMS.